2015
DOI: 10.1177/1060028015596415
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Methylphenidate on the Frequency of Stuttering

Abstract: This study showed that the participants had an objective statistically significant decrease in the frequency of stuttering with MPH, and this was not the case with placebo. This was also the case for a reduction in stutter moments when reading out loud and speaking spontaneously. However, this result was not subjectively perceived by the participants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In 2012, Devroey et al published a case report describing a healthy 18‐year‐old who had suffered from stuttering since childhood, and who experienced relief of stuttering symptoms after receiving MPH in a clinical trial designed for other purposes . Further to this report, Rabaeys et al (from the same institution) reported a randomized double‐blind crossover trial designed to reproduce this finding . They included 15 healthy young persons with developmental stuttering, who were treated by a single dose of MPH or placebo.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…In 2012, Devroey et al published a case report describing a healthy 18‐year‐old who had suffered from stuttering since childhood, and who experienced relief of stuttering symptoms after receiving MPH in a clinical trial designed for other purposes . Further to this report, Rabaeys et al (from the same institution) reported a randomized double‐blind crossover trial designed to reproduce this finding . They included 15 healthy young persons with developmental stuttering, who were treated by a single dose of MPH or placebo.…”
Section: Discussionmentioning
confidence: 93%
“…A statistically significant improvement in objective measures of stuttering was observed with MPH. Rabaeys et al suggested that MPH could be used to treat stuttering. In this study, it should be noted that subjects with ADHD, narcolepsy, and those with psychogenic or neurogenic stuttering were excluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Abnormal dopamine activity in the basal ganglia has been shown to be strongly associated with stuttering [11], and it is hypothesized that an imbalance in dopamine activity may be linked to stuttering [12,13]. This hypothesis is also supported by several case reports and studies discussing the use of methylphenidate for patients with ADHD [8,[14][15][16]. It is reported that the use of methylphenidate successfully reduced stuttering in an 18-year-old patient [15].…”
Section: Discussionmentioning
confidence: 96%
“…Five drugs in the top 20 drug–stuttering associations with the highest disproportionality in VigiBase are drugs prescribed for the treatment of ADHD ( Table 1 ). The paradoxical usage of the very same drug methylphenidate (acting via the dopamine pathway) in experimental treatment of stuttering ( 25 ) is dealt with below.…”
Section: Discussionmentioning
confidence: 99%